The Effect of Technological Transformation and Work Stress on Organizational Performance with Work Engagement as Mediator - Danny Indra Martohap Manullang; Eka Yudhyani; Evi Kurniasari Purwaningrum (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
In the era of rapid technological advancement, work engagement has emerged as a critical factor influencing both individual and organizational performance. Defined as a positive mental state characterized by vigor, dedication, and absorption, work engagement can enhance productivity and overall performance. However, work stress resulting from excessive job demands may hinder these outcomes. This study aims to examine the effects of work stress and technological transformation on organizational performance, with work engagement as a potential mediator. Employing a quantitative approach, the research uses a Structural Equation Modeling (SEM) design. The study involved 80 employees of the Immigration Office Class I TPI Samarinda, selected through purposive sampling. Data were collected using questionnaires measuring technological transformation, work stress, work engagement, and organizational performance, and analyzed using SmartPLS 4.0. The findings indicate that technological transformation positively affects both work engagement and organizational performance, while work stress negatively impacts work engagement but does not directly influence performance. Moreover, work engagement does not mediate the relationships studied. The study concludes that effective stress management and optimized technology adoption are key to enhancing organizational performance.